Implementasi Komunikasi Interpersonal Petugas Kawasan Parawisata Halal di Kawasan Danau Toba di Sumatera Utara - Simalango, Eka Susanti; Azhar, Anang Anas (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to find out tourists that Lake Toba is designed as one of the halal tourist destinations in Indonesia, but there is rejection among the community, especially tourism managers in the Lake Toba area. Rejection occurs because the community considers it to be contrary to the traditions and culture of the Batak tribe that have existed for generations. The purpose of this study is to find out how much halal tourism is in Lake Toba. The implementation of halal tourism is difficult to find around Lake Toba tourism because the majority are non-Muslims. So for Muslim tourists it is difficult to find halal tourism with places and dishes that are according to Islamic law. For Muslim tourists who travel, many still use the facilities provided as is. Tourists visiting Lake Toba are more Muslim than non-Muslim, but it is very minimal to find halal tourism. The study also showed that effective interpersonal communication involves direct interaction between officers and tourists, with officers providing clear and accurate information about halal services.